Ad hoc routing and time synchronization protocol for data collection on wireless sensor networks - Co, Kimberly Jane Y. (Animo Repository, 2021)
The Internet of Things (IoT) is rapidly growing as a topic of research and conversation. It envisions a world where everyday objects are connected through interacting with different communication protocols and the Internet to provide applications and services that aims to improve human life. This includes monitoring applications such as environment, healthcare, and military, which may need real-time gathering and delivery of data. As such, much of these applications are typically implemented through Wireless Sensor Networks (WSN). However, complications may arise due to the lack of proper coordination, communication, monitoring, and management of nodes in the network. This paper proposes an ad hoc routing and time synchronization protocol for data collection on WSN. A hybrid packet-based time synchronization is introduced, wherein reference time is sourced from the sink node (centralized) and sourced from the adjacent nodes (distributed). The time synchronization process is integrated into the routing and data transmissions in the network as it lessens overheads and transmission exchanges, which would be beneficial for large-scale WSN. Finally, the protocol's performance was evaluated using a realistic low-cost WSN testbed. The proposed time synchronization algorithm has achieved better synchronization accuracy compared to the TPSN algorithm, as seen in the multiple topology scenarios. Although the initial synchronization from the one-way synchronization adds extra overhead processing, nodes can quickly synchronize with their reference node compared to the TPSN, which has to perform multiple message exchanges with its reference node before it becomes synchronized.